108k views
2 votes
Use Gauss-Jordan row reduction to solve the given system of equations. HINT [See Examples 1-6.] (If there is no solution, enter NO SOLUTION. If the system is dependent, express your answer in terms of x, where

y = y(x).)
5x − 3y = 7
10x − 6y = 14

1 Answer

3 votes

Answer:

y = 5/3x -7/3

Explanation:

Subtracting twice the first equation from the second gives a row of zeros, indicating the system is dependent. Solving the first equation for y gives:

5x -7 = 3y

y = 5/3x -7/3 . . . . y in terms of x

_____

You could write the solution as ...

(x, y) = (x, 5/3x -7/3)

User Darshan Patel
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.